If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 3 + -2x = 2 Reorder the terms: 3(-4 + x) + 3 + -2x = 2 (-4 * 3 + x * 3) + 3 + -2x = 2 (-12 + 3x) + 3 + -2x = 2 Reorder the terms: -12 + 3 + 3x + -2x = 2 Combine like terms: -12 + 3 = -9 -9 + 3x + -2x = 2 Combine like terms: 3x + -2x = 1x -9 + 1x = 2 Solving -9 + 1x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 1x = 2 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = 2 + 9 1x = 2 + 9 Combine like terms: 2 + 9 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| 13x+6=13x-6 | | -16+5x=-2(x-6) | | 6b^2=-12b+18 | | -x-7=-1 | | -84+9x=120-3x | | 13x+100=180 | | 4+16m-2=9m+114-7m | | 9x^2-31x+24=0 | | -2x-16=3h-6 | | (8-3i)(2+7i)= | | -2p-1=5p-8 | | x^2+4=9x | | 6-(-30)= | | 30-18=6x | | 4a+10=10 | | y-8=0.14(x+9) | | =3(x-3.8)(x+1.2) | | 2(x-1)=5x-14 | | 187=-11x+55 | | 10-2h=3 | | 5(3c+2)=4(5c-10) | | 2cotx+sec^2x=0 | | 6(7-2p)=-38-2p | | -9.01-(-8.57)= | | -6x-10=8+5(8-7x) | | -84=7k | | 4(3c-6)=36 | | 13x+40=180 | | 30+150g=500 | | 5(2c-6)=40 | | -z+6z-10=15 | | 26=5x-4(4x+10) |